Hubungan Antara Motivasi Belajar dengan Prestasi Akademik Siswa di MTs Ex PGA Univa Medan (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the relationship between learning motivation and student academic achievement at MTs EXPGA. This research uses a quantitative approach with a correlational design. The sample used was 292 students, with an average student academic achievement score of 92. Data was collected using a questionnaire to measure learning motivation and academic value data obtained from student report cards. Data analysis was carried out using the Pearson correlation test to determine whether there was a significant relationship between learning motivation and academic achievement. The research results show that there is a significant positive relationship between learning motivation and student academic achievement at MTs Ex PGA, which shows that the higher the learning motivation, the better the academic achievement achieved. This research provides evidence that learning motivation plays an important role in determining students' academic success.